UJI PENDUGAAN BAKTERI COLIFORM PADA MINUMAN JAJANAN DI SEKITAR KAWASAN PENDIDIKAN TINGGI JATINANGOR - Azizah, Rini Nur; Quddus, Ati Atul; Kuswardhani, Liana; Lathifa, Cempaka; Lathifah, Mila Nur; Syarqiyah, Zainul; Khoerunnisa, Jihan Dila; Fauziyyah, Yasmien Hanifah (Pasundan Food Technology Journal (PFTJ), 2025)
The snack drinks sold around higher education areas, including Jatinangor, are often at risk of contamination by pathogenic bacteria such as Coliform. Coliform is an important indicator for assessing the cleanliness and safety of beverages, and its presence may indicate contamination from the environment, polluted water, or poor sanitation during production and serving. The high activity levels of students and the abundance of street vendors increase the chances of contamination if hygiene standards are not followed. Snack drinks in this area are often under-monitored, from the provision of clean water, storage of raw materials, to handling by vendors, which raises the risk of diseases such as diarrhea and gastrointestinal infections. This study focuses on examine the detection of coliform bacteria in snack beverage for sale around the higher education area of Jatinangor. This test will give a summary of the safety level about the beverages also assist in efforts to prevent and enforce hygiene standards by vendors. The study results are also expected to provide policy recommendations that support the improvement of hygiene standards for snack drinks in the area, as well as provide useful information for local governments and health authorities to oversee food safety in public areas. This research aims to raise awareness among vendors and consumers concerning the necessity of maintaining hygiene in the preparation as well as consumption of beverages relatig to prevent health risks.